Increasing Amounts of Secondary Metabolites and Medicinal Compounds in Callus Culture of Moringa Oleifera (Lam.) Using Abiotic Elicitors - Abed, Ashwaq S.; Ismail, Eman Noaman; Majeed, Duha M.; Al-Jibouri, Abedaljasim M. Jasim (Iraqi Journal of Science, 2023)
Moringa oleifera Lam. tree has often been considered a medicinal and economical plant for its nutritional and medicinal properties. This study is intended to use plant tissue culture and elicitation technologies to increase secondary metabolites in the callus cultures of the M. oleifera. Young nodal segments were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of plant growth regulators (PGRs). A combination of 1.5 mg/l NAA plus 0.5 mg/l TDZ resulted in a high callusing rate (70%) with the largest size. Various concentrations of Salicylic acid (SA) and Methyl jasmonate (MeJa) were individually added to the growth medium to evaluate their impact on the biomass of callus cultures, DPPH antioxidant activity, and accumulation of some flavonoids. Results indicated that all elicitors doses reduced weights and growth index of callus. While DPPH assay recorded high significant values at high concentrations of SA and MeJa compared to other treatments. HPLC analysis revealed that every concentration of SA and MeJa used led to rising flavonoids content, including Baicalin, Rutin, Hesperidin, Rosmarinic acid, Quercitrin, Quercetin, and Kaempferol. It should be noted that 20 mg/l MeJa gave the highest flavonoid content compared to the control and other treatments.  In conclusion, the in vitro elicitation by SA or MeJa can improve beneficial biological substances like flavonoids and other antioxidant compounds in Moringa callus cultures.